PERAN MAHASISWA KAMPUS MENGAJAR 7 MELALUI INOVASI PEMBELAJARAN DIGITAL TERHADAP KEMAMPUAN LITERASI DAN NUMERASI SISWA KELAS VIII DI SMP NURUL KHALIL - Elvina Camelia; Lutfiatul Fuddah; Febi Lusiana Marta; Alicia Dewi Nazarina; Rina Tut Jayati; Zainur Rasyid Ridlo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Technology has fundamentally altered how we obtain, distribute, and utilize information. Technology makes learning more flexible and adaptive in the classroom, which creates the potential for more innovative and successful teaching strategies. Through campus teaching programs, among other means, students are anticipated to be able to actively contribute to the improvement of Indonesian education as change agents. After around four years in operation, the campus teaching program has generated seven classes. This study examines the potential impact of campus students teaching seven at Nurul Khalil Middle School on the reading and numeracy proficiency of the student body, as measured by the grade 8 students' AKM test results. The primary focus of this research, which is being conducted utilizing a classroom action research paradigm, is the pupils of Nurul Khalil Middle School. We ascertain the level of pupils' literacy and numeracy ability through the use of documentation, observation techniques, and the AKM test. Together with tables and graphs showing the research findings, we also explain the data acquired using descriptive approaches.